Projected Changes to Spring and Summer Precipitation in the Midwestern United States - Grady, Kevin A.; Chen, Liang; Ford, Trent W. (Frontiers in Water, 2021)
Spring and summer precipitation are both important factors for agricultural productivity in the Midwest region of the United States. Adequate summer precipitation, particularly in the reproductive and grain fill stages in July and August, is critical to corn and soybean success. Meanwhile, excessive spring precipitation can cause significant planting delays and introduces challenges with weed and pest management, and soil erosion and compaction. However, uncertainty especially in future summer precipitation changes, translates to uncertainties in how the joint distributions of spring and summer precipitation are expected to change by mid- and late-century across the Midwest. This study examines historical and projected changes in the characteristics of spring and summer precipitation in the Midwest using 12 dynamically downscaled simulations under the high-emission representative concentration pathway (RCP 8.5) from the NA-CORDEX project. Historical increases in spring precipitation and precipitation intensity are projected to continue into the mid- and late-century across the region, with strong model agreement. By comparison, projected changes in Midwest summer precipitation are more modest than for spring and have much less model agreement. Despite a projected 3- to 4-fold increase in the frequency of wet springs by late-century, relative to the model ensemble historical average, the lack of substantial and robust projected change in summer precipitation results in only a small increase in the risk of dry summers following wet springs in the Midwest by mid- and late-century.